Non-Stocking Criterion - Fenske, R. W. (Management Science, 1968)
Contemporary inventory management attempts to make two critical inventory decisions—the order quantity and the order point. This type of analysis presupposes that stocking of the item is economically justified. Quite obviously this will not always be the case and inventory managers have had to turn to rules of thumb which are highly inflexible and consequently these rules often suggest exactly the opposite decision from that which should be made. The profit under conditions of both stocking and non-stocking can be analytically determined and then compared in a breakeven-type analysis. The intersection point or inventory cutoff level determines the minimum demand which will justify stocking the item and is derived along with a graphical representation. Two variations are provided—one for the manufacturer who produces to stock and one for the wholesaler or retailer who orders to stock.